Value Conflicts in Counseling Muslim LGBT Clients: Muslim Counselors' Experiences - Syed Mahmood, Syarifah Rohaniah; Ssekamanya, Siraje Abdallah (Atlantis Press, 2020)
The counselling profession has an affirmative stance towards LGBT clients. It is contradicting to the religious beliefs upheld by majority counsellors in the Muslim society. The difference between the stance of the counselling profession and religious beliefs create value conflicts among Muslim counsellors from the mainstream group. A grounded theory approach was used to explain how Muslim counsellors experience value conflicts in counselling Muslim LGBT clients. In-depth interviews were conducted with six counsellors at Public Institutions of Higher Education (PIHE) in Peninsular Malaysia. The findings revealed that the Muslim counsellors experienced three types of value conflicts; conflicting goals, conflicting roles, and conflicting interests. In overcoming the conflicts, they used three strategies; seeking information, prioritizing religious over professional values, and balancing between personal and professional interests.